2016
DOI: 10.1142/s021964921650012x
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Future of the Public Sector: Insights into a Swedish Municipality’s Dealing with Knowledge Management and Succession Planning

Abstract: The ageing workforce soon leads to a number of retirements in government organisations that will put the knowledge basis at risk. Addressing this point the present study provides an analysis and evaluation of a Swedish municipality's dealing with the aspects of knowledge management and succession planning against the background of demographic developments and the increased relevance of knowledge. It reports¯ndings based on semi-structured interviews conducted with executive sta® of the municipality. Results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…KR. As the issue of aging workforce and multigenerational workforce along with “war for talent “caught the attention of researchers, more empirical work was conducted in this domain proposing KR frameworks (Levy, 2011), strategies (Harvey, 2012; Daghfous et al , 2013; Massingham, 2014; Bratianu and Leon, 2015; Durst and Bruns, 2016; Sumbal et al , 2017), organizational and behavioral factors (Martins and Meyer, 2012) and major challenges (Bessick and Naicker, 2013; Aggestam et al , 2014; Agarwal and Islam, 2015; Sumbal et al , 2017). Further empirical research on KR has led to more industry-specific work such as critical types of knowledge lost in various industries (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…KR. As the issue of aging workforce and multigenerational workforce along with “war for talent “caught the attention of researchers, more empirical work was conducted in this domain proposing KR frameworks (Levy, 2011), strategies (Harvey, 2012; Daghfous et al , 2013; Massingham, 2014; Bratianu and Leon, 2015; Durst and Bruns, 2016; Sumbal et al , 2017), organizational and behavioral factors (Martins and Meyer, 2012) and major challenges (Bessick and Naicker, 2013; Aggestam et al , 2014; Agarwal and Islam, 2015; Sumbal et al , 2017). Further empirical research on KR has led to more industry-specific work such as critical types of knowledge lost in various industries (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, existing literature emphasizes the need for organizations to identify who has what knowledge in the organization (Davenport and Prusak, 1998; Durst and Wilhelm, 2011; Sumbal et al , 2018; Wang et al , 2022). And if the knowledge of an individual turns out to be critical for the development of the company, it should think about measures to retain this knowledge (Levy, 2011; Durst and Bruns, 2016; Sumbal et al , 2021). Failure to retain critical knowledge can result in knowledge leakage, knowledge attrition or in the worst case knowledge loss (DeLong, 2004; Durst and Ferenhof, 2016); which can significantly impair organizational activities (Massingham, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wadeson and Ciccotosto (2013) noted the continued lack of succession planning within small professional practices. Durst and Bruns (2016) pointed to the need for further research on succession planning strategies in different geographical locations and different public organizations. Santora et al (2015) also noted the need for more research regarding succession planning, within various national contexts.…”
Section: Lack Of Succession Planningmentioning
confidence: 99%
“…Globally, today's organizations operate in an environment of constant change. According to Domínguez-CC and Barroso-Castro (2017), 21st-century organizations are characterized by ever-increasing global competition and constant Bruns (2016) and Santora et al (2015). To help fill this gap, the researcher aimed to conduct a qualitative single-case study to determine how government executives perceive the strategies for the current succession planning process, which include a competency model, and the needed changes within the Ministry of Education in The Bahamas.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widely accepted importance of knowledge management in increasing the efficiencies and effectiveness of government functions (Durst and Bruns, 2016; Gangeswari et al , 2015; Khilji and Roberts, 2015), Massaro et al (2015), in their review of literature on knowledge management, observed that few authors have laid focus on knowledge management within governments/public sector. This demonstrates that more studies are needed to develop a cohesive body of literature in this area.…”
Section: Literature Reviewmentioning
confidence: 99%